Policing intimate partner violence in Victoria (Australia): examining police attitudes and the potential of specialisation - Segrave, Marie Therese (The Australian and New Zealand journal of criminology, 2018)
The adequacy of police responses to intimate partner violence has long animated scholarly debate, review and legislative change. While there have been significant shifts in community recognition of and concern about intimate partner violence, particularly in the wake of the Victorian Royal Commission into Family Violence, it nonetheless remains a significant form of violence and harm across Australian communities and a key issue for police, as noted in the report and recommendations of the Royal Commission. This article draws on findings from semi-structured interviews (n = 163) with police in Victoria and pursues two key inter-related arguments. The first is that police attitudes towards incidents of intimate partner violence remain overwhelmingly negative. Despite innovations in policy and training, we suggest that this consistent dissatisfaction with intimate partner violence incidents as a policing task indicates a significant barrier, possibly insurmountable, to attempts to reform the policing of intimate partner violence via force-wide initiatives and the mobilisation of general duties for this purpose. Consequently, our second argument is that specialisation via a commitment to dedicated intimate partner violence units - implemented more consistently and comprehensively than Victoria Police has to date - extends the greatest promise for effective policing of intimate partner violence in the future.